Hubungan Usia Dan Tingkat Pendidikan Dengan Pengetahuan Ibu Tentang Seksualitas Dalam Kehamilan Di Wilayah Kerja Puskesmas Talang Rimbo Lama Kabupaten Rejang Lebong Tahun 2023 - Neng Nita Iswandari; Murwati Murwati; Tita Septi Handayani (Jurnal Multidisiplin Dehasen (MUDE), 2023)
Pregnancy leads to fundamental changes in all body systems. The transition period of pregnancy can affect physical, emotional, cognitive, and sexuality patterns (Sagiv, 2012). The purpose of the study was to find out the relationship between age and education with the knowledge of pregnant women about sexuality in pregnancy in the working area of the talang rimbo lama health center, Rejang Lebong district in 2023. This type of research is analytic research using this type of research is analytic research using a cross-sectional design (Hidayat, 2012). The population of this study were all pregnant women in 2023 totaling 223 people, the number of samples in this study were 69 respondents. The results of this study indicate that almost half of the respondents 33 (47.8%) were 36-45 years old, more than half of the respondents 42 (60.9%) had secondary education, more than half of the respondents 51 (60.9%) had sufficient knowledge, there was a relationship between age and knowledge of pregnant women at Talang Rimbo Lama Health Center, Rejang Lebong Regency in 2023.There is a relationship between education and knowledge of pregnant women at Talang Rimbo Lama Health Center, Rejang Lebong Regency in 2023. It is recommended that the results of this study be used as the basis for health promotion strategies regarding sexuality during pregnancy, where health workers can explain sexuality patterns, changes in sexual desire in each trimester, inform you about the impact of sex on pregnancy, discuss when to limit sexual intercourse during pregnancy, and suggest sexual positions that can be practiced.